Natural dimethyl sulfide gradients would lead marine predators to higher prey biomass - Owen, Kylie; Saeki, Kentaro; Warren, Joseph D.; Bocconcelli, Alessandro; Wiley, David N.; Ohira, Shin Ichi; Bombosch, Annette; Toda, Kei; Paranhos Zitterbart, Daniel (Communications Biology, 2021)
Finding prey is essential to survival, with marine predators hypothesised to track chemicals such as dimethyl sulfide (DMS) while foraging. Many predators are attracted to artificially released DMS, and laboratory experiments have shown that zooplankton grazing on phytoplankton accelerates DMS release. However, whether natural DMS concentrations are useful for predators and correlated to areas of high prey biomass remains a fundamental knowledge gap. Here, we used concurrent hydroacoustic surveys and in situ DMS measurements to present evidence that zooplankton biomass is spatially correlated to natural DMS concentration in air and seawater. Using agent simulations, we also show that following gradients of DMS would lead zooplankton predators to areas of higher prey biomass than swimming randomly. Further understanding of the conditions and scales over which these gradients occur, and how they are used by predators, is essential to predicting the impact of future changes in the ocean on predator foraging success.
CRIS-Team Scopus Importer:2021-02-12